A new transmission strategy to achieve energy balance and efficiency in wireless sensor networks. (26th August 2020) - Wang, Yanli; Feng, Yanyan
Energy balancing and energy efficiency are very important in prolong network life. In wireless sensor networks, cooperative MIMO technology has become a research hotspot in recent years. The appropriate cooperative nodes can transmit data efficiently. Meanwhile, energy harvesting pays attention to the transmission process of network also. This paper presents the selection of cooperative nodes and cluster nodes, which offers energy balance. The node is not only the transmitter of information, but also the transmitter of energy. In addition, the paper also focuses on how to obtain the optimal energy efficiency with proposed resource allocation algorithm. Simulation results show that when cluster nodes and the cooperative nodes are more balanced, the selection algorithm realises the energy balance. The energy efficiency increases rapidly with the amount of transmitted power, and tends to be stable when it reaches 3 dBm. The cooperative MIMO technology is adopted to obtain higher network utility.